Cerebral sinovenous thrombosis in children with nephrotic syndrome: systematic review and one new case - Konopásek, Patrik; Piteková, Barbora; Krejčová, Vlasta; Zieg, Jakub (Frontiers in Pediatrics, 2023)
The aim of this review is to provide clinicians with characteristics of children with nephrotic syndrome and cerebral sinovenous thrombosis (CSVT).We have reviewed 37 articles of pediatric cases and provided 1 new case. PRISMA guidelines were followed.Results: Sixty-two patients were included in the review. CSVT was more common in males, usually occurred within 6 months of nephrotic syndrome onset and was found more often in outpatients. The superior sagittal sinus was the most common sinus affected. Non-contrast computed tomography was the most frequent radiologic study performed, with 30% of results negative for CSVT. Headache and vomiting were the most common symptoms while neurologic symptoms were less frequent. Anticoagulation treatment was strongly inconsistent throughout the literature. Thrombosis outcomes were favorable. The most common possible risk factors were corticosteroid treatment, proteinuria and hypoalbuminemia. Four children had a genetic predisposition diagnosed after thrombosis. No markers for anticoagulation prophylaxis seemed to be relevant for the majority of thrombosis occurring in outpatients.Prophylactic anticoagulation does not seem reasonable to prevent CSVT. Knowledge of nonspecific symptoms and of nephrotic syndrome being a state of hypercoagulation and early use of appropriate radiologic study seem to be of major importance.